Genesis 32: 23–33 as Jacob’s Divinization in Light of Ancient Near Eastern Ontology - Hubler, Caitlin Joy (The catholic biblical quarterly, 2025)
How might understanding the semantic range of אלהים affect interpretation of theophanic biblical texts like Jacob’s encounter at the Jabbok in Gen 32:23-33? Questions of divine ontology are so fundamental to interpretation that they are often overlooked, but neglecting culturally specific understandings of divinity often leads to the retrojection of anachronistic categories onto the biblical text. In contrast to some forms of Western metaphysics, which understand the possession or lack of divine status to be an essential and unchangeable fact, literary sources throughout the ancient Near East reveal a more fluid understanding of the divine-human spectrum. In light of ancient Near Eastern ontology, I argue that Jacob’s encounter at the Jabbok describes the process of his divinization.